2018
DOI: 10.1002/dvdy.24661
|View full text |Cite
|
Sign up to set email alerts
|

MMP14 Regulates Cranial Neural Crest Epithelial‐to‐Mesenchymal Transition and Migration

Abstract: The results demonstrate that MMP14 is critical for neural crest EMT and migration, partially through regulating the levels of cadherins. Developmental Dynamics 247:1083-1092, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 66 publications
3
34
0
1
Order By: Relevance
“…This conclusion is supported by the identification of ERG + SMA + cells with active SMAD2 signaling within the infarct and by the results with in vitro experiments showing that addition of neutralizing anti-TGFβ1 antibody to EC-Mφ co-cultures abolished EndMT. Our findings are in line with the role of MT1-MMP as an activator of epithelial to mesenchymal transition (EMT) in other pathophysiological contexts such as development, cancer, and lung fibrosis ( Garmon et al, 2018 ; Nguyen et al, 2016 ; Xiong et al, 2017 ). Interestingly, a recent scRNAseq study carried out on healthy and post-infarcted hearts identified a subset of post-MI Mφs with a HIF1α-dependent signature, which specifically upregulated Mmp14 expression ( Dick et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion is supported by the identification of ERG + SMA + cells with active SMAD2 signaling within the infarct and by the results with in vitro experiments showing that addition of neutralizing anti-TGFβ1 antibody to EC-Mφ co-cultures abolished EndMT. Our findings are in line with the role of MT1-MMP as an activator of epithelial to mesenchymal transition (EMT) in other pathophysiological contexts such as development, cancer, and lung fibrosis ( Garmon et al, 2018 ; Nguyen et al, 2016 ; Xiong et al, 2017 ). Interestingly, a recent scRNAseq study carried out on healthy and post-infarcted hearts identified a subset of post-MI Mφs with a HIF1α-dependent signature, which specifically upregulated Mmp14 expression ( Dick et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion is further supported by the identification of ERG + SMA + cells with active SMAD2 signaling pathway within the infarction and by the results obtained in in vitro experiments. Our findings are in line with the role of MT1-MMP as an activator of epithelial to mesenchymal transition (EMT) in other pathophysiological contexts such as development, cancer, and lung fibrosis (Garmon et al, 2018;Nguyen et al, 2016;Xiong et al, 2017). Interestingly, a recent scRNAseq study carried out on healthy and post-infarcted hearts identified a subset of post-MI Mφs with a HIF1α-dependent signature, which specifically upregulated Mmp14 expression (Dick et al, 2019).…”
Section: Mφ-derived Mt1-mmp Induces Endmt After MIsupporting
confidence: 86%
“…1G). This result was verified with an in vitro degradation assay, where neural tubes (transfected with AQP-1 FL or pMES) were plated on top of fluorescently labeled gelatin (Garmon et al, 2018). After 40 hours of incubation, the assays were imaged, and average fluorescent intensity of the gelatin was quantified as a read out of degradation (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…The protocol was slightly modified by heating all the gelatin to 60 degrees Celsius so that there was no issue in room temperature and warm gelatin not mixing fully. To optimize cell adhesion, fibronectin was then added over the gelatin as previously described (Garmon et al, 2018). 15 neural tubes (transfected with either pMES or AQP-1 FL) were plated into each well with 500ul of media and incubated for 40 hours.…”
Section: Methodsmentioning
confidence: 99%